Composition and Operation of a Semi-Virtual Renewable Energy-based Building Emulator. Issue 1 (26th January 2018) - Kilpeläinen, Simo; Lu, Minyan; Cao, Sunliang; Hasan, Ala; Chen, Shuqin
This paper describes the composition and operation of a semi-virtual energy system and building emulator designed for studying hybrid grid interactions of a modern nearly-zero energy building. The system consists of a real part for energy production (PV panels and micro-wind turbine), storage (batteries and hot water storage tanks) and conversion (ground-source heat pump GSHP and electric heater) combined with a virtual part that models a single-family house in the computer simulation program TRNSYS. A Labview program is used for communication between the real and virtual parts. Measurement data from six periods selected for study between September 2015 and February 2016 are analyzed. The data indicate that during the study, the total electricity consumption was 1290 kWh, divided to 44/38/18% between household appliances, GSHP and electric heater, respectively. The local net production was 250 kWh, or 19% of the total demand. PV, which was heavily concentrated in fall, accounted for 54% of the production. Wind production was winter-centered. The electrical energy matching aspects of the system are represented with two indices: OEFe (on-site electrical energy fraction), the fraction of the building electrical demand covered by local production, and OEMe (on-site electrical energy matching), the ratio of the building's self-consumption to the total local production. The matching capability of the energy system was found poor due to daily and seasonal mismatches between production and demand. The small net production compared to demand led to small OEFe and large OEMe values overall.